Ovipositional preference of oriental fruit fly bactrocera dorsalis hendel (Diptera: Tephritidae) on Mango (Mangifera indica L. cv. Chokanan) - Salmah, Mohamed; Nur Azura, Adam; Rita, Muhammad; Hong, Lau Wei; Hamdan, Ahmad (2017)
The oriental fruit fly, Bactrocera dorsalis Hendel, is one of the most problematic tephritid fruit flies and an agriculturally-important pest due to the severe damages caused in commercial fruits such as mango (Mangifera indica L.). The species is known to be able to develop eggs in different stage of ripening fruits. Therefore, this study is aimed to determine the ovipositional preference of B. dorsalis on different ripening stages of Chokanan mango. Fertilized B. dorsalis female flies were exposed to three different Chokanan mango ripening stages (i.e unripe, ripe and fully-ripe) for 24 hrs in no-choice and choice experiments. Results in the no-choice experiment showed that was no significant difference (P>0.05) on the puparia recovery among the three ripening stages. However, a high number of pupae were recovered from fully-ripe fruits (27.60±8.87 pupae) followed by ripe (18.20±7.59 pupae) and unripe fruits (4.60±3.03 pupae). Various parameters such as adult emergence, the percentage of adult emergence, and male and female emergence also showed no significant difference (P>0.05) among the stages. In choice experiment, the results were recorded similar with no-choice experiment in which there was no significant difference (P>0.05) of the number of pupae among the three ripening stages but relatively more pupae were recovered from fully-ripe fruits (35.8±28.5 pupae) compared to ripe (28.0±16.9 pupae) and unripe fruits (13.2±5.54 pupae). The adult emergence, percentage of adult emergence, and male and female emergence also showed no significant difference (P>0.05) among the stages. In conclusion, this study shows that a fully-ripe Chokanan fruit was relatively preferred by B. dorsalis females to oviposit eggs whilst unripe fruit stage was the least preferred. This finding may enhance the management control practices of B. dorsalis by the farmers.